The role of instability-enhanced friction on 'anomalous' electron and ion transport in Hall-effect thrusters. (15th December 2017) - Lafleur, Trevor; Chabert, Pascal
Abstract: Using a self-consistent 2D particle-in-cell (PIC) simulation, we investigate the electron transport in Hall-effect thrusters. The PIC simulation is explicit in time and models the axial and azimuthal directions of a thruster without using any artificial parametric or geometric scaling factors. The applied discharge voltage and external magnetic field causes electrons to drift in the azimuthal direction, and this drives an instability in the plasma that produces large amplitude oscillations in both the plasma density and azimuthal electric field. A Fourier transform in time and space shows that the oscillations follow a dispersion relation similiar to that for an ion acoustic instability (in agreement with a recent kinetic theory). Correlated with the presence of this instability is an enhanced electron cross-field transport; even in the absence of electron-wall collisions and secondary electron emission. The amplitude of plasma density oscillations (but not electric field oscillations) is found to decrease significantly in a region just downstream of the thruster exit (before then increasing again), and reaches levels similar to those measured experimentally with collective light scattering techniques. By taking relevant velocity moments of the electron distribution function in the PIC simulations, we reconstruct each term in the electron momentum conservation equation and demonstrate that 'anomalous' electron transport can be explained entirely due to an instability-enhanced friction force between electrons and ions. This friction force acts as an additional momentum loss allowing electrons to cross the magnetic field, and as an accelerating force causing ions to rotate azimuthally in the same direction as the electrons. Clear evidence of ion-wave trapping in the instability electric field is observed.